Factors influencing contract farming participation among saffron farmers in Iran - Sedighi, Navid Taghizadeh (2015)
Saffron has a special importance and position in the agricultural sector as the most important and valuable export crop but results of the contracts related to this product indicate that farmers do not show much of interest in contract farming participation. The statistics shows more than 40% of farmers who have concluded contracts have revoked them in later stages. Considering the importance of saffron in Iran’s agriculture sector, benefits of marketing and farming of saffron as it is stated before and the role of contract farming in reducing risks and increasing productivity and improvements in the supply chain, have made contract farming a good solution to promote saffron farming in Iran. This study is to examine the factors influencing the participation of contract farming of saffron in Iran. It aims firstly, to identify the current marketing practices of saffron in Iran, secondly to determine the factors which motivate contract farmers to participate in contract farming; thirdly to identify the determinants of saffron farmers participating in contract farming, fourthly to compare 3 group of farmers over 3 years and lastly to examine the extent to which demographic characteristics will influence farmers opinion on effectiveness of contract farming. The study conducted a survey on saffron farmers by using a structured questionnaire. The survey was conducted in the main saffron producing province of Khorasan (Iran) in 2013 (Torbat heydarye, Ghaen and Birjand). The study utilized a cluster random sampling method. A total of 415 saffron farmers were interviewed. One hundred and ninety five saffron farmers were independent farmers, 108 farmers with canceled contract and the remaining (112) were contract farmers. Our findings have supported the fact that saffron farmers in Iran have maintained the traditional marketing practices as they are still dependent on the suppliers. Besides this, saffron farmers still base their decisions by considering the amount of profit they obtain through contract farming. It is nevertheless observed that saffron farmers continue to face the same production and marketing problems compared to dependent Farmers. The main production issues confronting saffron farmers are a lack of technical services and productivity, which had adversely increased the cost of saffron production. The main marketing issue is price fluctuation of saffron and support from government and private companies which has resulted in an uncertain profit margin for farmers. Factor analysis is carried out to identify latent factors that influence saffron farmers with their participation in contract farming. Findings reveal six very important factors for saffron farmers participating in contract farming, which are commitment,production support, trust, satisfaction, technical support and productivity. Furthermore,findings indicate four factors influencing independent farmers’ willingness to not participate in contract farming, as independency, own market access, relationship with suppliers and productivity. In addition the six factors which influence farmers to cancel their contracts are dissatisfaction, miscommunication, not being committed, not being cooperative, no technical or production support, poor market access. In order to test the significance of the demographic contribution and the effect of contract farming on saffron farming in Iran, the multinomial logit was applied. Multinomial logit findings have revealed that age, education, and profit are the main variables for the effectiveness of contract farming for the saffron farmers. Farmers with higher education participate more in contract farming and also younger farmers are motivated to engage in contract farming to gain inputs, services and credits associated with it. On the other hand profit remains the important variable for farmers to stay independent. Farmers are getting more educated but still income plays vital roles for them. Therefore policy makers need to provide better credit services, insurance, incentives and technological equipment in order to attract more farmers to join in the contract farming. Moreover providing advisory services and training can be helpful in encouraging more farmers to get involved in contract farming by being exposed to the benefits of these activities.